Eating disorders in children and adolescents - the current state of knowledge - Mandera-Grygierzec, Amanda; Kostrzewska, Paulina; Szuster, Ewa; Pawlikowska-Gorzelańczyk, Anna; Lebioda, Aneta (Journal of Education, Health and Sport, 2022)
Introduction. Eating disorders (ED) are a group of severe mental health disorders with high prevalence, mortality and associated morbidity. The most common eating disorders are anorexia nervosa, bulimia nervosa and binge-eating disorder. Objective. The aim of the study was to evaluate prevalence, risk factors, clinical manifestation as well as complications for proper diagnostic and treatment of eating disorders. Materials and method. The literature review included articles from Google Scholar databases and PubMed. Articles published in 2013 or later were mainly considered. Brief description of the state of knowledge. The prevalence of eating disorders vary according to gender. There are a variety of risk factors that can be divided into family history, individual and possible triggers. The most common risk factors include family history of mental disorders. Studies have shown that premorbid overweight is more frequent in male. In the diagnosis of eating disorders, the ICD-10 and DSM-5 classification is used. Complications of this disease can manifest itself from various systems of the body. Proper cooperation between the pediatrician and the patient is very important. Treatment of eating disorders focuses on psychotherapy, especially family-based treatment. Worse results are obtained due to underdiagnosis and late initiation of treatment. Summary. Pediatricians are the first healthcare professionals which have contact with young patients, so education about the first symptoms and consequences of not receiving appropriate treatment is essential.